PENGEMBANGAN KARAKTER KONSERVASI UNTUK MAHASISWA BIOLOGI PROGRAM PPG-SM3T - Ridlo, Saiful (Jurnal Pendidikan Biologi, 2016)
Department of Biology, State University of Semarang has been appointed as one of the organizers of the Professional Teacher Education for scholars who have taught at the front, outermost, and lagging (PPG-SM3T) of Indonesia since 2013. The University was determined to hold lectures using Competency and Conservation Based Curriculum (CCBC). There are 11 conservation values of a character which wants to be developed as an identifier the university graduates profile. Values precondition character are piety, clean, neat, comfortable, and well mannered. This study aimed to describe the development of the character of the conservation values for PPG-SM3T students through Explore Roaming Around (JAS)-based learning approach. Data retrieved through observation while learning in the 1st semester and the questionnaire, and then exposed to narrated through a qualitative approach. The results showed that the Biology Education Study Program has been educated through exemplary, habiatuation and reinforcement, and reflective thinking in learning so as to develop nationalism, discipline, caring, polite, smart, responsible, democratic and religious attitude. Through the initiative of students has grown nationalist values but only 36% who say they want to return to front, outermost, and lagging area, and even then with the condition after 3-5 years can return to Java.